Semiconductor nanowires and nanotubes: from fundamentals to diverse applications - Grimes, Craig A. (2013)
Research in the field of semiconductor nanowires (SNWs) and nanotubes has been progressing into a mature subject with several highly interdisciplinary subareas such as nanoelectronics, nanophotonics, nanocomposites, biosensing, optoelectronics, and solar cells. SNWs represent a unique system with novel properties associated to their one-dimensional (1D) structures. The fundamental physics concerning the formation of discrete 1D subbands, coulomb blockade effects, ballistic transport, and many-body phenomena in 1D nanowires and nanotubes provide a strong platform to explore the various scientific aspects in these nanostructures. A rich variety of preparation methods have already been developed for generating well-controlled 1D nanostructures and from a broad range of materials. The present special issue focuses on the recent development in the mechanistic understanding of the synthesis, the studies on electrical/optical properties of nanowires and their applications in nanoelectronics, nanophotonics, and solar-energy harvesting.